Penile fracture caused by wild bear attack - Agarwal, A; KC, SR; Shrestha, P; Hirachan, S; Belokar, WK (Journal of College of Medical Sciences-Nepal, 2012)
Interaction between humans and wild animals has increased in recent times because of overlap of habitats. A proportion of this interaction is violent. Usually a large wild animal, like bear, causes significant bony trauma or attacks upper torso of body. We herein present a case of Asiatic black bear attack on an unusual part of body in a 40-year-old man near Nawalparasi, Nepal. The beast attacked genital region causing penile fracture. Patient was managed successfully in three stages. DOI: http://dx.doi.org/10.3126/jcmsn.v7i1.5973 JCMSN 2011; 7(1): 47-51